COSMETIC LASER LIPOSUCTION FATAL CASE (Journal of Forensic Medicine & Toxicology, 2015)
This is a case of fatal liposuction. A female 39 years old, had undergone laser liposuction for cosmetic purposes. She was having heavy built and wanted to improve her looks. She was operated in day care and was discharged on same day. She was found unconscious next morning by her mother at home. She was brought dead to hospital. At autopsy, it was found that she had fresh liposuction surgery marks and fresh cuts in fat at multiple sites in breast , abdomen , arms and thighs. There were some old healed liposuction marks. She died due to systematic fat embolism. This case is discussed with pros and cons of cosmetic liposuction surgery.
Keywords: Fat embolism; Laser Liposuction; cosmetic surgery; complications of liposuction